Production and Characteristics of Yeast Dextranase from Soil - Vestika Iskawati Wahidul Hijah; Titi Candra Sunarti; Anja Meryandini (HAYATI Journal of Biosciences, 2019)
The existence of dextran in sugar cane juice is a major problem in the sugar industry, causing substantial losses. Treatment of dextran through enzymatic hydrolysis using dextranase is highly recommended as the most suitable method at this time because this is more effective and more economical. This study investigated the production and characterization of dextranase from local isolate yeast to degrade dextran on sugar cane juice. The selected yeast was identified on the basis of molecular identification. Dextranase was produced from the culture with the best carbon and nitrogen sources then was characterized. Application of enzyme was also evaluated. As a selected isolate, F4 had the closest relationship with Pichia kudriavzevii. The highest production of dextranase was induced by the supplementation of glucose and combination of yeast extract and peptone. The enzyme had optimum working condition at pH 7, temperature at 30°C and it is more stable at 4°C of storage temperature. The cation Na+ played key role as co-factor while K+ and Ca2+ were detected as inhibitor of the enzyme. Dextranase from F4 isolate can hydrolyze dextran both in pure and in mixed dextran substrate, but with a lower hydrolysis rate.